Data from: Bionomics and insecticide resistance of the arboviral vector Aedes albopictus in northern Lao PDR - Tangena, Julie-Anne A.; Marcombe, Sebastien; Thammavong, Phoutmany; Chonephetsarath, Somsanith; Somphong, Boudsady; Sayteng, Kouxiong; Grandadam, Marc; Sutherland, Ian W.; Lindsay, Steve W.; Brey, Paul T. (2018)
In the last four decades there has been a staggering increase in the geographical range of the arboviral vector Aedes albopictus (Skuse, 1894). This species is now found in every continent except Antarctica, increasing the distribution of arboviral diseases such as dengue and chikungunya. In Lao PDR dengue epidemics occur regularly, with cases of chikungunya also reported. As treatment methods for arboviral diseases is limited, the control of the vector mosquitoes are essential. There is a paucity of information on the bionomics and resistance status of this mosquito for successful vector control efforts. Here we describe the bionomics and insecticide resistance status of Ae. albopictus in Laos to identify opportunities for control. Adult Ae. albopictus were collected using human-baited double bed net (HDN) traps in forests, villages and rubber plantations and tested for alpha- and flaviviruses with RT-PCR. Surveys were also conducted to identify larval habitats. Seven adult and larval populations originating from Vientiane Capital and Luang Prabang province were tested against DDT, malathion, permethrin, deltamethrin and, temephos following WHO protocols. Aedes albopictus were found throughout the year, but were six-fold greater in the rainy season than the dry season. Adult females were active for 24 hours, with peak of behaviour at 18.00 h. The secondary forest and rubber plantation samples showed evidence of Pan-flaviviruses, while samples from the villages did not. More than half of the emerged Ae. albopictus were collected from mature rubber plantations (53.9%; 1,533/2,845). Most Ae. albopictus mosquitoes emerged from latex collection cups (19.7%; 562/2,845), small water containers (19.7%; 562/2,845) and tyres (17.4%; 495/2,845). Adult mosquitoes were susceptible to pyrethroids, apart from one population in Vientiane city. All populations were resistant to DDT (between 27–90% mortality) and all except one were resistant to malathion (20–86%). Three of the seven larval populations were resistant to temephos ...